Penerapan Multiply With Carry Generator pada Proses Pembangkitan Kunci Algoritma Beaufort Cipher - Taronisokhi Zebua (Journal of Information System Research (JOSH), 2023)
The strength of the algorithm used in data security does not only depend on the complexity of the algorithm used, but lies in the randomness and complexity of the key solving used. The repetition of the same character in the formation of a key used by a data security algorithm is very vulnerable to attack, because it can make it easier for attackers to break the algorithm itself. One of the commonly used data security algorithms is the comfort cipher algorithm. The number of key characters needed in this algorithm is directly proportional to or equal to the number of characters of text or data that is secured. Using a number of key characters like this allows the repetition of the same characters, making it easier for attackers to find out the pattern of the keywords used. Based on this, random key generation is necessary to optimize the robustness of the algorithm used. Multiply with carry generator is a random number generation technique that has advantages in speed and length of randomization cycle so that it has more seed variations to the generated random numbers. This study describes how to apply this random number generation method to generate keywords used in the beaufort cipher algorithm, so that the keys used can be more optimal and more complicated for attackers to crack.